Atomic oxygen resistance of polyimide/silicon hybrid thin films with different compositions and architectures. (November 2014) - Lei, Xingfeng; Yao, Pan; Qiao, Mingtao; Sun, Wanlu; Zhang, Hepeng; Zhang, Qiuyu
Silicon (Si)-containing polyimides (PIs) with superior atomic oxygen (AO) resistance are promising materials for space applications. Here, in this study, we present the synthesis and characterization of eight Si-containing PI thin films and evaluate their AO durability. The resulting PI films exhibited high thermal stability and preferable AO resistance but showed slightly reduced mechanical performance relative to pristine PI. The highest optical transparency at 550 nm was observed for PI/octaaminopropylsilsesquioxane, while the lowest value was observed for PI/silica (SiO2 ) hybrids. X-Ray photoelectron spectroscopic study suggested that the topmost surface of PI was degraded at the early stage and an SiO2 inert protective layer was finally formed on the surface of hybrid films after AO exposure. It is found that Si-containing units of higher oxidation states and with higher Si/O molar ratio are favorable to improve the AO resistance. Dispersion of Si at molecular level contributes to improving anti-AO property as well as optical transparency of the prepared films. The characterization of scanning electron microscopy indicated a continuous SiO2 protective layer was crucial to prevent AO from eroding the bulk matrix.